Using popular epidemiology to empower community residing around integrate refi nery petrochemical complex (IRPC) industrial zones, Rayong Province, Thailand - Intawong, Chanthip; Phankote, Naiyana; Naewpana, Manusdaw (Biomedical Sciences and Clinical Medicine, 2016)
Objective This study aims at using Popular Epidemiology to empower community residing around IRPC Industrial zone to conduct health surveillance at Choeng Noen and Taphong Subdistrict, Meuang District, Rayong Province, Thailand, during March to May 2014 and March to September 2015. Methods The action research among using popular epidemiology to empower community was as followed: community leaders and health volunteers met with the participation of Sub-district Administrative Organization (SAO) and primary health care team in the area. After community meeting they prepared information such as a community map, patients’ name, address and disease diagnosed, equipment used for making a map and community survey. Diseases of interest were cancer and asthma, and questionnaire was designed accordingly. During community survey, we recorded the location of risk areas and patients using symbols on the map immediately. We made the focus group discussion for cluster analysis of patients associated with the risk factors and wind direction after survey. Then, we provided after action review and refl ected on using Population Epidemiology tool for health effects assessment and planning in the future. Results The eastern and southwestern regions of Choeng Noen Sub-district were closed to IRPC petrochemical industry zone. Patients in the community sometimes get chemical odors. There were a gas station, auto repairing shop, rest area for garbage trucks and ice making plant. We visited 3 asthma and 9 cancer patients. The east of Taphong sub-district was next to the IRPC petrochemical industry zone as well. There were a petrol station, garbage store and landfill and auto painting shop. We visited 11 cases of asthma and 9 cases of cancer. We analyzed the clusters of patients and found that the patients scattered around the IRPC industrial zone. However, it is unable to conclude that cancer and asthma were caused by air pollution from volatile organic compounds. We found many types of cancer not specific to exposure to Volatile organic compounds (VOCs) in the ambient air and insufficient number of cases. It is interesting to provide long-term surveillance. The community has learned about participation in community health analysis by using popular epidemiology. Conclusion The use of Popular Epidemiology to empower community requires cooperation between the communities, health care workers and SAO’s support in order to be achieved and sustained. The communities proposed to expand using Popular Epidemiology to other areas around industrial complex for community health surveillance and evaluation.